Characterization of the Mid Summer Drought in the Central Valley of Costa Rica, Central America - Alfaro Martínez, Eric J. (2013)
The IAS region is characterized by climate features of unique nature, one of them is the Mid-Summer Drought (MSD), “veranillo” or “canícula” in Spanish, an atmospheric attribute rarely observed in tropical regions. On the Pacific slope of Central America, the precipitation annual cycle is characterized by two rainfall maxima in June and September-October, an extended dry season from November to May, and a shorter reduced precipitation period during July–August (MSD), during July, the magnitude of trade winds increase and this is associated also with the Caribbean Low Level Jet (Amador, 2008), but characterization of these features using monthly data is difficult. In this work, three daily gauge stations records, e.g. La Argentina, Fabio Baudrit and Juan Santamaria, located in the Central Valley of Costa Rica were studied to characterize the MSD from 1937 to 2012. Among the aspects considered are the MSD Start (July 1), Timing (July 21), End (August 9), Intensity (7.2 mm/day), and Precipitation at the Minimum (4.1 mm). The modulation and seasonal predictability of these aspects by climate variability sources as Equatorial Eastern Pacific and Tropical North Atlantic was lately explored, including their interannual and decadal variability. Atlantic SST variability didn’t show statistical significant relationships. Particular study cases were selected to observe the synoptic conditions around Central America for different atmospheric variables, that because MSD signal strongly impact social and economic life in the region like energy (Puente de Mulas, Belen, Virilla, La Garita and Nuestro Amo dams are located there) and the agriculture sector (around 50% of the national coffee production). Additionally, Central Valley of Costa Rica, specially the Tarcoles river basin, hosts most of the Costa Rican population with the higher level of exposition and vulnerability to hydro- meteorological hazards, 53% of the Costa Rican population lives in that basin.